Listening Effort With Cochlear Implant Simulations. - Pals, Carina; Sarampalis, Anastasios; Başkenta, Deniz; Bacon, Sid; Healy, Eric (Journal of Speech, Language & Hearing Research, 2013)
Purpose: Fitting a cochlear implant (CI) for optimal speech perception does not necessarily optimize listening effort. This study aimed to show that listening effort may change between CI processing conditions for which speech intelligibility remains constant. Method: Nineteen normal-hearing participants listened to CI simulations with varying numbers of spectral channels. A dual-task paradigm combining an intelligibility task with either a linguistic or nonlinguistic visual response-time (RT) task measured intelligibility and listening effort. The simultaneously performed tasks compete for limited cognitive resources; changes in effort associated with the intelligibility task are reflected in changes in RT on the visual task. A separate self-report scale provided a subjective measure of listening effort. Results: All measures showed significant improvements with increasing spectral resolution up to 6 channels. However, only the RT measure of listening effort continued improving up to 8 channels. The effects were stronger for RTs recorded during listening than for RTs recorded between listening. Conclusion: The results suggest that listening effort decreases with increased spectral resolution. Moreover, these improvements are best reflected in objective measures of listening effort, such as RTs on a secondary task, rather than intelligibility scores or subjective effort measures.